Bacterial Communities of Diatoms Display Strong Conservation Across Strains and Time - Behringer, Gregory; Ochsenkühn, Michael A.; Fei, Cong; Fanning, Jhamal; Koester, Julie A.; Amin, Shady A. (Frontiers in Microbiology, 2018)
Interactions between phytoplankton and bacteria play important roles in shaping the microenvironment surrounding these organisms and in turn influence global biogeochemical cycles. This microenvironment, known as the phycosphere, is presumed to shape the bacterial diversity around phytoplankton and thus stimulate a diverse array of interactions between both groups. Although many studies have attempted to characterize bacterial communities that associate and interact with phytoplankton, bias in bacterial cultivation and consistency and persistence of bacterial communities across phytoplankton isolates likely impede the understanding of these microbial associations. Here, we isolate four strains of the diatom Asterionellopsis glacialis and three strains of the diatom Nitzschia longissima and show through metabarcoding of the bacterial 16S rDNA gene that though each species possesses a unique bacterial community, the bacterial composition across strains from the same species are highly conserved at the genus level. Cultivation of all seven strains in the laboratory for longer than one year resulted in only small changes to the bacterial composition, suggesting that despite strong pressures from laboratory culturing conditions associations between these diatoms and their bacterial communities are robust. Specific operational taxonomic units (OTUs) belonging to the Roseobacter-clade appear to be conserved across all strains and time, suggesting their importance to diatoms. In addition, we isolate a range of cultivable bacteria from one of these cultures, A. glacialis strain A3, including several strains of Shimia marina that appear closely related to OTUs conserved across all strains and time. Coculturing of A3 with some of its cultivable bacteria as well as other diatom-associated bacteria show a wide range of responses that include enhancing diatom growth. Cumulatively, these findings suggest that phytoplankton possess unique microbiomes that are consistent across strains and temporal scales.